Analisis Kondisi Perekonomian Indonesia 2020-2024 - Raysa Putri Nabila Hasibuan; Johan Paulo Negos Sinaga; Hannes Inmanuel Sinaga; Kristian Ronaldo Tampubolon; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The 2020–2024 period is a crucial time for the Indonesian economy, which is facing severe pressure due to the COVID-19 pandemic and global economic dynamics. This study aims to analyze the development of the national economic condition over the past five years through key macroeconomic indicators, such as Gross Domestic Product (GDP), Foreign Direct Investment (FDI), forest area, industrial sector contribution, high-tech exports, domestic credit, trade in goods, and gross national income per capita (GNI per capita). The method used is descriptive quantitative based on data from the Central Statistics Agency (BPS) and secondary sources from national and international institutions. The results show that despite a contraction in 2020 due to the pandemic, the recovery process has been rapid since 2021, with stable economic growth in the range of 5% until 2024. Increased GNI per capita, improved foreign investment flows, and the expansion of economic digitalization are key factors strengthening national resilience. However, challenges remain, such as a decline in the industrial sector's contribution and a reduction in forest area. These findings confirm that Indonesia's economic development is moving toward a structural transformation oriented toward sustainability, sector diversification, and social inclusiveness. Overall, the 2020–2024 period reflects a phase of recovery and restructuring of the economic foundations toward achieving the Vision of a Golden Indonesia 2045 with global competitiveness.